EVALUATION OF THE FUNCTIONAL STATE OF THE KIDNEYS OF NEWBORNS BORN TO MOTHERS WITH OPG GESTOSIS - Ishkabulova G. D. (Web of Journals Publishing, 2025)
40 newborns were examined, the functional state of the kidneys was assessed depending on the presence of OPG gestosis in pregnant women. It was revealed that all newborns have a decrease in diuresis, a decrease in the osmotic concentration of urine, which increases by the end of the first week of life, but does not reach the indicators of healthy children, while the most pronounced changes are observed in the group of children born to mothers with OPG gestosis, and are accompanied by azotemia, which is associated with catabolic processes in the body and reduced renal excretion of nitrogenous products.
Keywords: Newborns, kidneys, OPG gestosis in pregnancy.